Correlation Between Spinopelvic Sagittal Alignment Parameters and Low Back Pain: Spinopelvic Sagittal Alignment Parameters and Low Back Pain - Bilal, Muhammad; Janjua, Faizan Ali; Jan, Abdullah; Jatoi, Asif Ali; Qureshi, Muhammad Asad; Aslam, Ejaz (Pakistan Journal of Health Sciences, 2025)
Low back pain is a common musculoskeletal disorder with a major socioeconomic impact. Understanding its association with spinopelvic alignment may enhance diagnosis and treatment by identifying key biomechanical factors linked to symptom severity. Objectives: To assess the relationship among spinopelvic parameters and low back pain severity. Methods: This retrospective study was conducted at Bahria International Hospital, Rawalpindi, Pakistan, including 150 patients. Full-spine standing X-rays were used to assess sagittal vertical axis, sacral slope, pelvic tilt, pelvic incidence, and lumbar lordosis using Surgimap® software. A visual analog scale was used to measure the severity of the pain, and Pearson correlation analysis was performed to determine associations between spinopelvic parameters and LBP severity. Results: Pelvic tilt showed a positive correlation with lumbar pain, which is significant (r=0.52, p<0.001) and radicular pain (r=0.33, p=0.002). Sagittal vertical axis was also positively correlated with lumbar (r=0.47, p<0.001) and radicular pain (r=0.38, p=0.001). A significant negative correlation of lumber lordosis was exhibited with both lumbar (r=-0.49, p<0.001) and radicular pain (r=-0.41, p<0.001). No significant correlation was found for PI or SS. Conclusions: Pelvic tilt and sagittal vertical axis positively correlate with low back pain severity, whereas lumbar lordosis exhibits a protective role. These findings emphasize the importance of spinopelvic alignment in low back pain pathophysiology.